Prevalence of Anxiety, Depression and Stress among Antenatal Women attending a Tertiary Care Centre in Kerala during COVID 19 pandemic - Nageswaran Gomathy A; Devakumar Indu; Nambisan Bindu (Healthline, 2021)
Introduction: Anxiety, depression and stress can cause negative impacts on the foetus and pregnancy. The COVID19 pandemic provides a unique stressor requiring an assessment of its impact in the Indian set up. Objectives:1. To assess prevalence of anxiety and depression among antenatal women attending the antenatal OP at a tertiary care centre during COVID 19 pandemic using Hospital Anxiety and Depression Scale (HADS). 2. To determine stress perceived by antenatal women using the Perceived Stress Scale (PSS). Method: Antenatal women attending the outpatient clinic between November 2020 and January 2021 were consecutively enrolled into the study after obtaining consent and a semi-structured interviewer administered questionnaire was used to collect data. The outcome variables, including sociodemographic details, HADS and PSS scores, were analysed using SPSS software, and results expressed appropriately, with quantitative variables expressed as mean and standard deviation, and qualitative variables as proportions. Results: Prevalence of anxiety among antenatal mothers was estimated to be 39%, of which 87.8 % had income below the poverty line. Prevalence of depression was estimated to be 11.4 %. Stress levels were high in 41.9 % of the women. Anxiety showed a positive correlation with stress (correlation coefficient of 0.711). Conclusion: High prevalence of anxiety and stress among antenatal women, especially from poor income backgrounds, points to an urgent need for reassurance and counselling.